Features of selection and breeding work in carp growing - Karlova, L. V.; Karlova, L.; Karlova, Lina V.; Karlova, Lina Valentinovna; Karlova, Lina Valentunivna; Karlova, Lina; Карлова, Ліна Валентинівна; Lesnovska, O. V.; Lesnovskay, O. V.; Lesnovska, E. V.; Lesnovskay, E. V.; Lesnovska, O. W.; et al. (Дніпровський ДАЕУ, 2019)
Modern breeding work in fish culture provides a complex of organizational and fish farming measures aimed at improving of hereditary qualities and increasing the productivity of pond fish. These measures include technically correct growing and model keeping of fish, observance of the right methods of choice and selection, and provision its full nutrition at all stages of development. The main object of warm-water stable fish farming for today is carp. In the selection work with the carp, two problems are solved: improving the productive qualities at the expence of application of the method of nidification selection and creation of races, adapted to specific cultivation conditions. The differentiation of these tasks has conditional character, because in any case it is a question of improving productivity against the background of specific cultivation conditions. Thus, the implementation of the above-mentioned tasks will contribute to the development of breeding potential of Ukrainian carp races. Modern breeding work in fish culture provides a complex of organizational and fish farming measures aimed at improving of hereditary qualities and increasing the productivity of pond fish. These measures include technically correct growing and model keeping of fish, observance of the right methods of choice and selection, and provision its full nutrition at all stages of development. The main object of warm-water stable fish farming for today is carp. In the selection work with the carp, two problems are solved: improving the productive qualities at the expence of application of the method of nidification selection and creation of races, adapted to specific cultivation conditions. The differentiation of these tasks has conditional character, because in any case it is a question of improving productivity against the background of specific cultivation conditions. Thus, the implementation of the above-mentioned tasks will contribute to the development of breeding potential of Ukrainian carp races. Сучасна селекційна робота з рибної культури забезпечує комплекс організаційних та рибогосподарських заходів, спрямованих на поліпшення спадкових якостей та підвищення продуктивності ставкових риб. Ці заходи включають технічно правильне вирощування та модельне утримання риби, дотримання правильних методів вибору та відбору та забезпечення її повноцінного живлення на всіх стадіях розвитку. Основним об'єктом рибництва на сьогоднішній день є короп. У селекційній роботі з коропом вирішуються дві задачі: поліпшення продуктивних якостей за рахунок застосування методу селекційного відбору та створення риб, пристосованих до конкретних умов вирощування. Таким чином, реалізація вищезазначених завдань сприятиме розвитку племінного потенціалу українських коропових риб.
Особливості селекційно-племінної роботи при вирощуванні коропів
Карлова Ліна Валентинівна https://orcid.org/0000-0001-8213-8588 Лесновська Олена Володимирівна https://orcid.org/0000-0002-9027-6734
Keywords: rozvedennya; розведення; koropovі; коропові; breeding; селекція